Peran Guru dalam Memotivasi Belajar Siswa Kelas IV pada Mata Pelajaran Bahasa Indonesia di SDK Penilering Desa Balaweling 1, Kecamatan Solor Barat, Kabupaten Flores Timur - Patrisius Gelupa Werang; Imelda Oliva Wissang; Sirilus Karolus Keroponama Keban (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study aims to describe the role of the teacher in motivating the learning of fourth grade students in Indonesian subjects at Penilering Elementary School, Balaweling 1 Village, West Solor District, East Flores Regency. This research is a qualitative research. The research data was obtained directly from the research subjects as a data source, namely grade IV students at SDK Penilering Balaweling 1 Village, West Solor District, East Flores Regency totaling 13 students, and class IV teacher Mrs. Okpriasni, S, Pd, and school principal, Mrs. Maria Bunga Sawun, S.Pd. Data collection uses observation, interview, and documentation techniques. Data analysis using data analysis using data reduction techniques, data presentation, drawing conclusions or verification, and triangulation. The results showed that there was a teacher's role in increasing learning motivation in the Indonesian language subject for fourth graders of SDK Penilering, namely: (1) the teacher as a demonstrator by providing varied learning methods and using language that was easy for students to understand, (2) the teacher as class manager with paying attention to student concentration, and rolling seats, (3) the teacher as a facilitator and mediator by preparing various learning facilities and media, and (4) the teacher as an evaluator by giving gifts, grades, punishments and praise.